TANGGUNG JAWAB SOSIAL PERUSAHAAN: AKTUALISASI AJARAN JAUDATUL ADA (PENYELESAIAN YANG BAIK) DALAM BISNIS (STUDI KASUS BSM) - Rimi Gusliana Mais; Eko Ganis; Aulia Fuad Rahman; Aji Dedi Mulawarman (Jurnal Reviu Akuntansi dan Keuangan)
As a form of accountability for its economic activities, every company in the world must performCSR activities, including companies in Indonesia. Unfortunately, the values contained in current CSR reporting contain only secular activities, whereas Indonesia is a country with 200million Muslims who are entitled to use Islamic religious values in their lives that are includedin economic activities, including CSR. This study aims to find the appropriate Islamic valuesand can be applied in CSR activities. This study finds value in Islam that can be a referencecompany, in terms of this research is syariah bank, for CSR activities, namely the value ofJaudatul Ada (good settlement).Keywords: CSR, Islam, economy, Jaudatul ‘Ada